2023
DOI: 10.1002/ejhf.3048
|View full text |Cite
|
Sign up to set email alerts
|

The different risk of new‐onset, chronic, worsening, and advanced heart failure: A systematic review and meta‐regression analysis

Abdul Shakoor,
Sabrina Abou Kamar,
Jishnu Malgie
et al.

Abstract: Background and aimsHeart failure (HF) is a chronic and progressive syndrome associated with a poor prognosis. While it may seem intuitive that the risk of adverse outcomes varies across the different stages of HF, an overview of these risks is lacking. This study aims to determine the risk of all‐cause mortality and HF hospitalizations associated with new‐onset HF, chronic HF (CHF), worsening HF (WHF), and advanced HF (adv. HF).MethodsWe performed a systematic review of observational studies from 2012 to 2022 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…Patients in the new-onset HF and WHF cohorts included in this meta-analysis were older than patients in the other two categories. 4 However, the meta-regression approach showed that the risk differed across HF stages in spite of age adjustment (age adjusted odds of death 2.72 for new-onset HF, 3.58 for WHF and 5.15 for advanced HF). In contrast, women had a persistent higher mortality risk in comparison to men across all HF stages in the sex-specific subgroup sensitivity analysis.…”
Section: Influence Of Age and Sex On Heart Failure Stagingmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients in the new-onset HF and WHF cohorts included in this meta-analysis were older than patients in the other two categories. 4 However, the meta-regression approach showed that the risk differed across HF stages in spite of age adjustment (age adjusted odds of death 2.72 for new-onset HF, 3.58 for WHF and 5.15 for advanced HF). In contrast, women had a persistent higher mortality risk in comparison to men across all HF stages in the sex-specific subgroup sensitivity analysis.…”
Section: Influence Of Age and Sex On Heart Failure Stagingmentioning
confidence: 99%
“…The work by Shakoor et al 4 define WHF and new-onset HF. Of note, WHF patients received less frequently optimal medical therapy (angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers, or angiotensin receptor-neprilysin inhibitors) compared with CHF patients (74% vs. 96%), and had a similar percentage than those with advanced HF (74% vs. 78%).…”
Section: Clinical Heart Failure Staging: In Need For Accurate and Hom...mentioning
confidence: 99%
See 2 more Smart Citations